Morphological Process of COVID-19 Neologisms: A Study of Compounding - Nurhalimah Amiruddin; Abdul Hakim Yassi; Sukmawaty Sukmawaty (English Learning Innovation (englie), 2022)
This study investigates the compounding process in COVID-19 neologisms. It focuses on words that coexist with words synonymous with the COVID-19 pandemic and the level of public understanding of neologisms that will enter general acceptance through standard English dictionaries. This research is qualitative research. The data comes from Urban Dictionary as a non-standard dictionary involving the community as neologism makers. Data was collected from the first confirmed case of COVID-19 in China on December 8, 2019 to January 31, 2022. Each neologism that resulted from the compounding process with two constituent words was collected to get the most widely used identical word, then compounding by including these words would be analysed to know the results and also the score. We have been found that the lower the score obtained by neologisms with match results, the greater the expectation that neologisms can be accepted by the general public as a global language through standard English dictionaries. Vice versa, the higher the score obtained by neologisms, the smaller the expectations of neologisms can be accepted. However, neologisms with mismatch results are difficult to accept, and even the resulting scores cannot predict anything. Another fact that was found was the error result as a result of the absence of the definition referred to in the standard dictionary. From the overall analysis, nouns are the most used word class.